2012
DOI: 10.2134/agronj2012.0021
|View full text |Cite
|
Sign up to set email alerts
|

Sensor‐Based Insecticide Spraying to Control Cereal Aphids and Preserve Lady Beetles

Abstract: Lady beetles (Coccinella septempunctata) are one of the most effective predators of aphids (Sitobion avenae). Therefore, the development of plant protection technologies that do not lead to their eradication within the field is necessary. With a sensor‐controlled field sprayer, which determined in real‐time the plant biomass of a heterogeneous winter wheat field and, based on these measurements, also controlled the amount of applied insecticide, a variable rate spraying program was implemented. The insecticide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Other work recorded pesticide use reduction in perennial crops between 28% and 70% [118][119][120][121]. VRPA can also cause reductions in insecticide use by 13.4% in winter wheat [122], while spray overlap can be significantly decreased with impact on the total pesticide use [123].…”
Section: Ghg Emission Reduction Potential Through Vrpamentioning
confidence: 99%
“…Other work recorded pesticide use reduction in perennial crops between 28% and 70% [118][119][120][121]. VRPA can also cause reductions in insecticide use by 13.4% in winter wheat [122], while spray overlap can be significantly decreased with impact on the total pesticide use [123].…”
Section: Ghg Emission Reduction Potential Through Vrpamentioning
confidence: 99%
“…The biological diversity of large fields is maintained and subsequently it promotes the capacity of biological pest control. For example, a sensor‐controlled on‐line variable rate insecticide spraying in winter wheat to combat the aphid Sitobion avenae resulted in insecticide savings of 13% 5 . In this study the sensor CROP‐Meter did not detect the insects or their damage directly, but its signal was correlated with biomass and LAI.…”
Section: Indirect (Unspecific) Sensing: Detection Of Insect‐damaged Cmentioning
confidence: 76%
“…Other important component of precision agriculture, the pest-specific management has economic and environmental effects. In specific studies, it was reported that the variable rate spraying by sensor controlled technology reduced insecticide use by 13% on average while maintaining the biodiversity on agricultural fields (Dammer and Adamek, 2012). Considerable savings occur with fuel, seed, chemical and fertilizer.…”
Section: (360) 2019mentioning
confidence: 99%